2018
DOI: 10.3389/fphys.2018.00115
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Catapult ClearSky T6 Local Positioning System for Team Sports Specific Drills, in Indoor Conditions

Abstract: Aim: The aim of the present study was to determine the validity of position, distance traveled and instantaneous speed of team sport players as measured by a commercially available local positioning system (LPS) during indoor use. In addition, the study investigated how the placement of the field of play relative to the anchor nodes and walls of the building affected the validity of the system.Method: The LPS (Catapult ClearSky T6, Catapult Sports, Australia) and the reference system [Qualisys Oqus, Qualisys A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
95
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(105 citation statements)
references
References 41 publications
7
95
1
2
Order By: Relevance
“…Otherwise, no conclusions can be drawn as to whether the observed deviations result from the system's measurement inaccuracy or merely from differing data-processing decisions. In addition, the raw position might be the most unaffected variable and should be used as the primary variable to compare measurements between different positioning systems' acquisition technology [21]. It is for this reason that we decided to apply the very same data processing steps to both VICON's and TRACAB's raw data.…”
Section: Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, no conclusions can be drawn as to whether the observed deviations result from the system's measurement inaccuracy or merely from differing data-processing decisions. In addition, the raw position might be the most unaffected variable and should be used as the primary variable to compare measurements between different positioning systems' acquisition technology [21]. It is for this reason that we decided to apply the very same data processing steps to both VICON's and TRACAB's raw data.…”
Section: Data Processingmentioning
confidence: 99%
“…Accordingly, analysis of validity and reliability of EPTS has been subject to extensive research in recent years. While a large and ever-increasing number of GNSS and LPS validation studies can be found [7,8,[18][19][20][21][22], only a few studies are available that validated the measurement accuracy of football-specific video tracking systems. To date, two studies fulfil this criterion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A different method should be used to evaluate the accuracy of the position of players on the court or to estimate instantaneous velocities (real-time analysis). Only three studies have evaluated position data, and these studies used LPS-based technology with video analysis as a reference [5,18,19]. LPS and video analysis are costly and complex to use.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the reference system is based on fixed cameras and can therefore only acquire data in restricted areas [20]. In this sense, no studies have been found that have evaluated the accuracy of a tracking system in a complete field of play, where instead they only exist in confined and controlled spaces [3,5,18,19,21]. The capture volume is dependent on the maximum number of cameras and the field of view of each camera.…”
Section: Introductionmentioning
confidence: 99%